The Government Support on Women Entrepreneurial Intention Affected by Layoffs in Tourism Industry - Arina, Kristi Karla; Sumanti, Athina Isabella; Gradianto, Gabriel (E-Journal of Tourism; Volume 9 Number 1 (March 2022)DO - 10.24922/eot.v9i1.80576, 2022)
This study discusses the model of local government support to generate entrepreneurial intentions for women who have been laid off due to the Covid-19 pandemic. There are four government support as the intervention variable tested, financial support, assistance in design and production, supply chain coordination, and marketing and sales support. While the research object context is the internal locus and external locus of control, acting as exogenous variables. The survey used a questionnaire designed using a 5-point Likert scale. Questionnaires were distributed to women affected by layoffs who live in Minahasa Utara Regency, Sulawesi Utara Province, Indonesia, a total of 75 questionnaires were answered completely. Data analysis using Smart PLS. The results of data analysis show that, without government support intervention, women with an internal locus of control are more interested in becoming entrepreneurs than those with an external locus of control. Government support has a significant impact in generating entrepreneurial interest in women with internal and external locus of control. Women with an external locus of control are more motivated to become entrepreneurs, especially if they receive financial support, while women with an internal locus of control are more motivated to become entrepreneurs if they are supported in supply chain development. Government support for coordinating supply chains adds to the literature on external factors that have an impact on entrepreneurial intentions. The managerial implication of the findings of this study is the importance of the government's role, especially in financial support for women with external locus of control and supply chain support for women with internal locus of control.